UPAYA PEMBINA DALAM MENANGANI KEDISIPLINAN SISWA PESERTA EKSTRAKURIKULER OLAHRAGA DI SMA SE-KOTA BANDUNG - Arif Wahyudi (Jurnal Pendidikan Jasmani Indonesia, 2009)
This research has been inspired by the assumptions that learning process done by school sports (extracurricula) coach could handle student discipline. The problems in this research was what were the efforts done by the coach in handling student discipline in high schools in Bandung City which included strategies and discipline in the teaching and learning processes. The method of the research was discriptive research by survey. The data collection technique included closed questionaire with Likert scale. The population is school sport coach in high schools. A number of 30 partisipants were involved after they have been choosen by purposive random. The results show that the coach had 82% of absorbing power on the startegy component. This means that the strategies that they have been used are good. The coach said that the strategies were implemented to keep ready with the possibilities that indiscipline happens during the learning process. In addition, the coach had 80, 36% of absorbing power on the discipline component. It means that the discipline has been implemented in such a good way. The coach said that the discipline implementation was for decreasing the oppoertunity that indiscipline would occur during learning process. Those two components are the variable effort that has absorbing power 81,18%. It shows that the coach had good efforts in handling student discipline. Kata kunci: ekstrakurikuler, disiplin, siswa, strategi